Phaeohyphomycosis in China - He, Yun; Zheng, Hai-lin; Mei, Huan; Lv, Gui-xia; Liu, Wei-da; Li, Xiao-fang (Frontiers in Cellular and Infection Microbiology, 2022)
Background Due to more attentions paid to melanized fungi over the past few decades and under the background of the global coronavirus disease 2019 pandemic (COVID-19) the fact that the virus itself and the immunosuppressive agents such as glucocorticoids can further increase the risk of infections of deep mycoses, the number of patients with phaeohyphomycosis (PHM) has a substantial increase. Their spectrum is broad and the early diagnosis and treatments are extremely sticky. This study aims to more comprehensively understand the clinical features of phaeohyphomycosis in China over 35 years and to establish a more applicable systematical classification and severity grades of lesions to guide treatments and prognosis. Methods We reviewed 174 cases of proven phaeohyphomycosis reported in Chinese and English language literature from 1987 to 2021 and we also made the accurate classification definitions and detailed information about the epidemiology, species of clinical dematiaceous fungi, minimum inhibitory concentration values, clinical features, treatments, and prognosis. Results The mortality of cerebral, disseminated and pulmonary phaeohyphomycosis are 55%, 36%, and 25%. Nearly 19% of patients had poor quality of life caused by the complications such as disability, disfigurements, and blindness. The overall misdiagnosis rate of phaeohyphomycosis was 74%. Moderate to severe rashes are accounting for 82% of subcutaneous phaeohyphomycosis. The areas of the head and face are mostly affected accounting for 16% of severe rashes. Nearly 30% of invasive infections of phaeohyphomycosis are triggered by recurrent lesions. Voriconazole, itraconazole, amphotericin B deoxycholate (AmB-DOC), and terbinafine were most commonly used but diagnosis and treatments of phaeohyphomycosis remain challenging in reality. Conclusions Our classifications are likely to be more practical and easier to popularize, and there are still also plenty of characteristics in these non-specific lesions. There’re no significant variations in cure rates, or death rates between three grades of lesions. But patients with severe rashes have longer courses and lower effective rates.